Physicochemical characteristics of soils for agricultural and forestry use. Case: San Pablo de Tarugo, Chone – Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2022)
The aim of this research was determine the physicochemical characteristics of soils of agricultural and forestry use in San Pablo de Tarugo, Chone, province of Manabi, Ecuador. The descriptive analytical method and techniques such as interview and direct observation were used. Analysis of multielements (ammoniacal nitrogen, phosphorus, potassium, calcium and magnesium), texture, apparent density, pH, electrical conductivity, organic matter and color in samples of agricultural (cassava) and forest soil was performed. The texture of the agricultural soil is sandy clay, while the forest soil is loam; bulk density was 0.44 g/cm3 and 0.76 g/cm3 on forest floor, respectively; agricultural soil is acid (5.50) and forest soil is neutral (7.25); the multielements reflected similar values in both soils; and, in both soils, dark tones predominate. The electrical conductivity is lower in agricultural soil (216.67 uS/cm) since the forest soil reached 400.00 uS/cm; observing, the forest soil contains more than double the organic matter (30.00 %), evidencing different physicochemical characteristics in the analyzed soils.
Keywords: Analysis; Physicochemical characteristics; Agricultural soil; Forest soil